Improving the Activities and Learning Outcomes of Mathematics Content Students Using the Chief Model In Class V - Sukma Ayu Pratiwi; Herti Prastitasari (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Problem in study This is activities and results Study low students​ in learning Mathematics . The goal For describe teacher activity , analyzing enhancement activities , and results Study student . Types of research This using PTK. Subject study student class V SDN Alalak Selatan 1 Banjarmasin and implemented 4x meetings .​ Type of data used qualitative . Research result show that activities teachers experience enhancement from score 27 to 32 with